Librarians collaborate successfully with nursing faculty and a writing centre to support nursing students doing professional doctorates. (28th August 2020) - Bernstein, Matthew; Roney, Linda; Kazer, Meredith; Boquet, Elizabeth H.
Abstract: This study explores how a three‐way collaboration between a University library, writing centre and faculty created avenues of training and support for students within a Doctor of Nursing Practice (DNP) program in an American University. The role of each partner involved in the collaboration is discussed alongside the profile of the DNP students. Lesson planning and classroom techniques for DNP information literacy classes are described and feedback from the partners and the students are discussed. The study confirms that collaboration is effective in improving research and writing skills. D.I.